Influence of compressive stress on chloride transport in the interfacial zone of precast and cast‐in‐place concrete. (4th August 2020) - Zhao, Jie; Li, Fumin; Luo, Xiaoya
Abstract: The large number of interfacial zones of precast and cast‐in‐place concrete weakens the durability and resistance to chloride penetration of fabricated structures. This study investigated the chloride transport behavior in the interfacial zone of precast and cast‐in‐place concrete through long‐term wet–dry cycle experiments. The two influencing factors of compressive stress and distance to the interface were investigated. A chloride concentration test was conducted to investigate the chloride distribution profile, the chloride diffusion coefficient D app, and the surface chloride concentration C s, ∆x . The values of D app and C s, ∆x correlated with both the location in the interfacial zone and compressive stress, and both dependencies showed complex interactions. All specimens showed different degrees of this interfacial zone effect, which was weakened by compressive stress. Based on the test results, empirical models were developed (by regression) to quantify the dependences of D app and C s, ∆x to both compressive stress level and distance to the interface. Applicability of the models was verified.